Comparison of cryogenic and non-cryogenic droplet impact dynamics at low Weber numbers - Giovanni Tretola; Konstantina Vogiatzaki (Scientific Reports)
Abstract Cryogenic fluids are crucial in applications such as rockets, cryosurgery and energy storage, where they can come in contact with surfaces. Thus, their impact dynamics are of interest. Experiments under cryogenic conditions are very expensive and not always accurate, mainly due to limitations of equipment operating in very low temperatures. Although simulation tools can provide useful insights, currently very few commercial and open-source software tailored for ultra low temperature conditions exist. In this work we present a novel numerical framework used to provide insight into the impact dynamics of cryogenic droplets with solid surfaces. Our aim is to explore whatever conclusions for droplet spreading dynamics from the current literature for droplets at non-cryogenic conditions can be applied to cryogenic droplets as well. We explore different impacting conditions, varying the initial impact velocity, of cryogenic and non-cryogenic cases, while maintaining the same Weber, Ohnesorge and Reynolds numbers between cryogenic and non-cryogenic cases. The impact on a solid surface is investigated first for a water droplet and then for a liquid oxygen droplet moving into gaseous nitrogen. For the latter, the ambient temperature and pressure are below the oxygen critical point, limiting the investigation at a sub-critical regime. The algebraic volume of fluid method with adaptive mesh refinement is employed. Numerical treatments to improve the interface description are also implemented. The simulations have been performed in OpenFOAM with a newly developed code. The results obtained are analysed both qualitatively and quantitatively, comparing the droplet morphology evolution for the two fluids. Differences are observed mainly in the receding stage, once the droplet has reached the maximum spreading, with the receding stage of the cryogenic case characterised by a faster dynamic.